2015
DOI: 10.1371/journal.pone.0123856
|View full text |Cite
|
Sign up to set email alerts
|

From Reef to Table: Social and Ecological Factors Affecting Coral Reef Fisheries, Artisanal Seafood Supply Chains, and Seafood Security

Abstract: Ocean and coastal ecosystems provide critical fisheries, coastal protection, and cultural benefits to communities worldwide, but these services are diminishing due to local and global threats. In response, place-based strategies involve communities and resource users in management have proliferated. Here, we present a transferable community-based approach to assess the social and ecological factors affecting resource sustainability and food security in a small-scale, coral reef fishery. Our results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 83 publications
3
83
0
Order By: Relevance
“…These results are in line with findings from Campbell et al (2013) who found the importance of socio-economic and institutional coherence as key factors in smallscale fisheries management. In similar fashion, the results of this study are also supported by findings from Kittinger et al (2015) who emphasize the importance of social and ecological factors for sustainable fisheries.…”
Section: Relationship Among Variablessupporting
confidence: 88%
“…These results are in line with findings from Campbell et al (2013) who found the importance of socio-economic and institutional coherence as key factors in smallscale fisheries management. In similar fashion, the results of this study are also supported by findings from Kittinger et al (2015) who emphasize the importance of social and ecological factors for sustainable fisheries.…”
Section: Relationship Among Variablessupporting
confidence: 88%
“…Nonetheless, small-scale fishers share major concerns about regulatory constraints on fishing, marginal incomes, and a lack of alternative livelihood sources [1, 75, 76]. Ruiz [28] found that fishing is satisfying as an occupation, yet fishers can be disgruntled about the level of earnings, the condition of marine resources and the performance of management institutions.…”
Section: Discussionmentioning
confidence: 99%
“…In Hawaii, the great majority of fishing for coral reef fishes is non-commercial [34–36], typically for subsistence, recreation and/or sharing with wider social networks [35]. Expanded estimates of non-commercial fishery catch and effort expansions are generated by the Marine Recreational Information Program (MRIP), but those are only available at statewide level (i.e.…”
Section: Methodsmentioning
confidence: 99%